HUBUNGAN BEBAN KERJA DENGAN PERILAKU CARING PERAWAT - Santi, Witni Alicia; Larira, Dina Mariana; Pondaag, Ferlan Ansye (JURNAL KEPERAWATAN, 2025)
Introduction: Caring nurse behavior is an important part and also an interpersonal process that includes health services, building a trustworthy and close relationship between patients and care givers. The heavy workload affects the performance of nurses, especially related to the implementation of caring behavior during nursing care. This condition makes it difficult for nurses to perform optimally in providing comfort, affectionate attention, caring, maintaining health, encouraging, empathetic, showing interest, loving, trusting, protecting, always there if needed, supporting, touching and ready to help and visit patients. Purpose: To determine the relationship between workload and caring behavior of nurses in the Inpatient Room of Budi Setia Langowan Hospital. Method: This type of research uses a cross sectional study approach with quantitative research methods, using the Spearman Rho Test, the sample used in this study was 33 nurses. Data collection techniques in this study were carried out using questionnaires, analysis techniques in this study using SPSS. There was a relationship between workload and caring behavior of heavy nurses with (p-value = 0.002) and Correlation strength of (r value = -0.514). Conclusion: There is a relationship between workload and caring behavior of nurses in the inpatient room of Budi Setia Langowan Hospital. Keywords: Workload, caring behavior, nurse